Faktor-faktor yang Mempengaruhi Kinerja Karyawan Bagian Produksi PT. Buana Spring Foam Purwokerto - Anggita Oktaviani Putri; Harsuti Harsuti; Fatwa Zuhaena (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
This research aims to determine and analyze the influence of job satisfaction, work discipline, work motivation, and work environment on employee performance at PT. Buana Spring Foam Purwokerto. This research is included in the quantitative research category. The population of this study consisted of 90 employees and 78 respondents were selected using probability sampling techniques with the proportionate stratified random sampling method.Research findings show that the performance of employees of PT. Buana Spring Foam Purwokerto is significantly and partially influenced by the following factors: job satisfaction, work discipline, work motivation, and work environment. The implications of this research suggest that companies must continue to pay attention to the promotion system, discipline, provide motivation, rewards or appreciation, and create a comfortable work environment and good relations between employees to improve their performance.